Green Waqf Education and Literacy for Worshippers of the Pekanbaru Mujahadah Mosque to Facilitate Sustainable Development - Wali Saputra (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
The objective of this community service initiative is to enhance the comprehension and awareness of the worshippers at the Pekanbaru Mujahadah Mosque regarding the concept of green waqf as a mechanism of Islamic social finance that is instrumental in promoting sustainable development. The execution of this initiative is necessitated by the observed deficiencies in the literacy concerning productive waqf and the inadequate application of waqf for the purposes of environmental enhancement and economic empowerment of the community. The methodology employed in conducting this community service comprises four principal stages, namely: (1) the preparatory stage, which encompasses coordination with the mosque, the development of educational materials, and the preliminary assessment of the worshippers' level of waqf literacy; (2) the implementation stage, which involves socialization efforts, interactive training sessions, and group discussions focused on the concepts, advantages, and practical applications of green waqf; (3) the evaluation and reporting stage, which includes the assessment of participants’ knowledge advancement and the compilation of reports detailing the outcomes of the activities; and (4) the Sustainability Evaluation Results Stage, which examines the sustainability impact of the program through the engagement of worshippers in green waqf initiatives and the potential for its realization at the mosque level. The findings from the activities indicated a substantial enhancement in the worshippers' grasp of the green waqf concept, with an increase from an average of 55.4% prior to the initiative to 87.8% subsequent to the initiative. Participants also demonstrated considerable enthusiasm for the execution of environmentally-focused green waqf initiatives, such as waqf-based reforestation and waste management programs. Furthermore, small groups of worshippers have been established, demonstrating commitment to advance the green waqf program within the mosque community. Consequently, this initiative significantly contributes to the enhancement of sharia financial literacy, the broadening of the productive waqf function, and the promotion of sustainable principles of Islamic social finance at the community level of the mosque.